Patriotism and cosmopolitanism in the work of Hans Christian Andersen - Arnaudova, Svetlana (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
The paper deals with the cultural relations between Denmark and Germany in the first half of the 19th century, which formed the binational and bicultural identity of Hans Christian Andersen and his conviction that the muse of the new age is „cosmopolitan“. European Romanticism is seen as a transnational project despite the nationalist constructions of concepts such as nation and identity. The transnational movement of goods related to industrialization in the 19th century and the new relations of exchange and consumption, which led to a more intensive and fruitful meeting between the Scandinavian languages and literatures, is also in the focus. Attention is drawn to the links between Romanticism and the Enlightenment, emphasizing that the contradictions between the two epochs are not as insurmountable as is usually assumed.